To survive. Climate migration through the eyes of the Global South - Macura-Nnamdi, Ewa; Malinowska, Magdalena; Cygan-Adamczyk, Weronika (No Limits, 2025)
In the face of intensifying climate change, the phenomenon of migration – or rather displacement – is taking on a new meaning, especially from the perspective of the Global South. Researchers analyse literature and art from African and Caribbean countries to bring to light the less-heard but extremely important voices of the communities most affected by the climate crisis. They draw attention to the difference between the Western narrative on migration and local adaptation strategies, which often express hope, determination and a desire to create a new future – also through African futurism. In their view, climate-induced displacement is not only a geographical migration but also a cultural and symbolic change that redefines humanity's relationship with the planet and other forms of life. It is a voice that, if heard, could be the key to a more just and sustainable future.